Early to Middle Miocene Dissectec Arc of Karangsambung Area: A Case Study of Waturanda and Penosogan Formations Provenance - Safira, Faradhea; Purwasatriya, Eko Bayu; Gibran, Akhmad Khahlil (Journal of Earth and Marine Technology (JEMT), 2023)
This study undertakes a comprehensive analysis of the geological conditions within a specific region, with a dual objective. Firstly, it aims to detail the geophysical attributes, structural aspects, and formation processes of the region. Secondly, it strives to establish a connection between the provenance, or origin, of the sedimentary materials in the region and its geological characteristics. The primary subjects of the research are the Waturanda and Penosogan Formations. These formations were selected due to their unique geological properties that offer insights into the geological history of the region. The primary method employed in the study was petrographic analysis. This technique, involving a microscopic examination of rocks, facilitated a detailed investigation into the rock samples from both formations, highlighting their mineralogical constitution and overall textures. The study also involved a thorough examination of the original rock or parent material of the Waturanda and Penosogan Formations. This analysis provided important information about their inherent geological attributes and formation processes. One of the key findings was the identification of the tectonic environment in which these formations were developed. The study revealed that the tectonic setting was a magmatic arc, specifically a dissected arc. This significant insight into the geological conditions has profound implications for understanding the geological evolution and history of the region, thereby enriching our knowledge of Earth's dynamic geological processes.